Basal and Dynamic Leptin Secretion: Association with Cardiometabolic Risk and Body Weight Trajectories in African-Americans and European-Americans - Ebenibo, Sotonte; Edeoga, Chimaroke; Owei, Ibiye; Dagogo-Jack, Sam (Frontiers in Endocrinology, 2018)
Background: Fasting plasma leptin levels reflect fat mass, but dynamic leptin responses to secretagogues, and the influence of race/ethnicity, have not been well-studied. Here, we compared basal and stimulated leptin levels in relation to cardiometabolic risk and weight trajectories in black and white subjects. Subjects and Methods: We studied 254 (127 black, 127 white) normoglycemic adults enrolled in the Pathobiology of Prediabetes in a Bi-racial Cohort (POP-ABC) study. At baseline and annually, POP-ABC participants underwent physical examination, OGTT, and measurements of body fat (DEXA), fasting plasma leptin, insulin, cortisol, lipids, and leptin secretory response to single-dose (2 mg) dexamethasone (dex). The interactions among basal and stimulated leptin and changes in adiposity/cardiometabolic measures during the ensuing year were then analyzed. Results: The mean (±SD) fasting leptin level (50.6 ± 47.7 vs. 39.5 ± 37.6 ng/ml, P=0.004) and BMI (31.9 ± 7.14 vs. 29.0 ± 7.66 kg/m2, P=0.0043) were higher in black women vs. white women, but similar in black men vs. white men (Leptin: 12.4 ± 2.07 vs. 11.1 ± 1.40 ng/ml; BMI: 29.4 ±7.68 vs. 28.1 ± 4.23 kg/m2). The peak leptin response to dex (~200% baseline) did not differ significantly by gender or race. Total body fat correlated positively with fasting leptin (r=0.81, P<0.0001) and inversely stimulated leptin levels (r= -0.26, P<0.0001). Fasting leptin was unrelated to 1-yr change in weight or fat mass, whereas stimulated leptin levels were significantly associated with 1-yr trajectories in weight (P=0.0016) and total fat mass (P=0.0035). Stimulated leptin levels also had significant interactions with insulin sensitivity (HOMA-IR, P=0.01), triglycerides (P=0.0078), fasting glucose (P=0.027), systolic BP (P=0.037) and hsCRP (P=0.027). Conclusions: We found no significant ethnic disparities in basal or dynamic leptin secretion in relation to adiposity. Fasting leptin levels were not associated with 1-year weight change, while stimulated levels showed weak though significant association with 1-year weight change.